Economic and Sustainable Development of Entrepreneurial Practices : A Philanthropic Approach of Islamic Finance in India - Irfan, Mohammad; Tanwar, Sunita (Arthshastra Indian Journal of Economics & Research, 2018)
The biggest contribution of Islamic economics, commerce, and business is to entrepreneurship. There are many successful Muslim entrepreneurs in the world. Islam always encourages Muslims to be innovative, creative, and to have active participation as entrepreneurs. The objective of this study was to provide an overview of the conceptual cum - practical aspects of Islam on entrepreneurship and venture capital in India. The well - known contracts of raising and mobilizing venture capital in Islam are known as mudarabah (special partnership) and musharaka (equity partnership). These contracts are functioning under assistance of multi cooperative credit societies in different states of India. It was concluded that there is a huge potential for Islamic products in India, which is the third largest Muslim populated country. It was suggested that by keeping eyes on Shariah compliant products, one can seek future business opportunities in India.